Towards the construction of a gender geography of the city. Plural forms of inhabiting and meaning urban spaces in Latin America (2018)
This article provides a review of the main contributions in the theoretical production and urban research accomplished from a gender and feminist perspective in Latin America. The objective is to show how men and women inhabit and signify the city in different ways and to understand how they simultaneously form part of both the social construction of the urban space and the social construction of the genre. Forwhich a review of academic articles, research, books and working documents is made from the nineties to the present. Organizational theoretical concepts, thematic cores and research problems are identified, as well as challenges and horizons for the construction of a feminist urban geography in the region.